Non-alcoholic fatty liver disease (NAFLD): A comparative study of clinico-socio-demographic characteristics among two diverse Indian population - Prangya Paramita Sahoo; Mukta Singh; Dibyalochan Prahraj; Dawesh Prakash Yadav; Ayaskanta Singh; Kanishka Uthansigh; Girish Kumar Pati (Romanian Medical Journal)
Objectives. The prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing not only in India but also globally. The aim of this observational study was to determine the clinico-pathological findings of NAFLD patients in two different geographic populations in India. Material and methods. This hospital-based cross-sectional study involved 140 consecutive patients with NAFLD from four centers, primarily diagnosed by ultrasound in Uttar Pradesh (Varanasi) and Odisha (Khordha). Clinical and sociodemographic data were collected from each patient of both the states and were compared. Outcomes. The study findings revealed that most of NAFLD patients were males (71.4%), aged around 39.6±10.86 years, with BMI indicating overweight (27.68 ± 4.25 Kg/m2). Patients from Uttar Pradesh (UP) had non-significantly higher rates of elevated transaminase levels [SGOT/SGPT- 40.2 (41.53)/47.35(60.93) IU/L], compared to those from Odisha [SGOT/SGPT-26(23.15)/29(45.40) IU/L]. Too cases of Odisha had non-significantly higher mean triglyceride levels compared to patients of UP. There was a significant difference in family type in-between the 2 regions (p=0.000), with Odisha having more number of nuclear families compared to UP. Cases from Odisha had non-significantly higher per capita monthly income (41.891 ± 43.23 INR) compared to UP (34.276 ± 27.66 INR). Statistically significant dietary preferences, were noticed in-between the 2 states with majority from Odisha favoring non-vegetarian diets (90.6%) compared to Uttar Pradesh (75.06%). Conclusions. Patients from Odisha had higher per capita monthly income, history of higher non-vegetarian diet consumption, higher hypertriglyceridemia and lesser transaminases compared to cases from Uttar Pradesh.